2019
DOI: 10.1002/eji.201847801
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD93 is an apoptotic cell opsonin recognized by αxβ2

Abstract: Efferocytosis is essential for homeostasis and prevention of the inflammatory and autoimmune diseases resulting from apoptotic cell lysis. CD93 is a transmembrane glycoprotein previously implicated in efferocytosis, with mutations in CD93 predisposing patients to efferocytosis‐associated diseases. CD93 is a cell surface protein, which is proteolytically shed under inflammatory conditions, but it is unknown how CD93 mediates efferocytosis or whether its efferocytic activity is mediated by the soluble or membran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 67 publications
2
34
0
Order By: Relevance
“…Our analysis of IIMs identified a reduction in the expression of multiple genes involved in the efferocytosis of apoptotic cells and the phagocytosis of microbial pathogens ( Figures S3). RT-PCR confirmed that the a x integrin, a receptor for both complement-opsonized pathogens and CD93-opsonized apoptotic cells, was downregulated in IIMs ( Figure 4A) (63). Unexpectedly, integrin-linked kinase, which was downregulated in the patients analyzed in our microarray analysis ( Figure 1C) was not downregulated in the patient cohort used for our RT-PCR assays ( Figure 4B).…”
Section: Gata2 Overexpression Impairs Phagocytosis and Efferocytosissupporting
confidence: 55%
“…Our analysis of IIMs identified a reduction in the expression of multiple genes involved in the efferocytosis of apoptotic cells and the phagocytosis of microbial pathogens ( Figures S3). RT-PCR confirmed that the a x integrin, a receptor for both complement-opsonized pathogens and CD93-opsonized apoptotic cells, was downregulated in IIMs ( Figure 4A) (63). Unexpectedly, integrin-linked kinase, which was downregulated in the patients analyzed in our microarray analysis ( Figure 1C) was not downregulated in the patient cohort used for our RT-PCR assays ( Figure 4B).…”
Section: Gata2 Overexpression Impairs Phagocytosis and Efferocytosissupporting
confidence: 55%
“…Our group recently discovered that atherosclerotic macrophages upregulated the hematopoietic transcription factor GATA2 in response to modified lipoproteins ( 78 ). Upregulation of GATA2 led to the downregulation of multiple proteins required for efficient efferocytosis, including downregulation of the efferocytic receptor α X integrin, multiple signaling molecules required for these receptors function including multiple Src-family kinases, impaired efferosome-lysosome fusion via decreased expression of Rab7, and impairment in multiple degradative pathways needed for the degradation of apoptotic cargos including lysosomal acidification ( 10 , 78 ). Interestingly, mutations in the GATA2 gene has been linked to increased risk of cardiovascular disease in human cohort studies ( 79 ).…”
Section: Cell Signaling and Transcriptional Regulationmentioning
confidence: 99%
“…Gas6, MFGE8, CD93) that bind to ligands found on the plasma membrane of apoptotic cells (e.g. phosphatidylserine), much of the processes downstream of apoptotic cell internalization such as intracellular trafficking of apoptotic cell cargo and cellular responses to internalized of apoptotic cell contents are either thought to be wholly analogous to phagocytosis or to be poorly understood ( 1 , 7 10 ). Strikingly, efferocytes such as macrophages can distinguish between normal apoptotic cells and those infected with an intracellular pathogen, despite the fact that much of the contents of an infected apoptotic cell (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Soluble CD93 has been suggested to induce differentiation of monocytes by as yet undefined mechanisms [168]. A role for soluble CD93 in the process of efferocytosis has been proposed, whereby cleaved CD93 binds to apoptotic cells via the CTLD in a Ca 2+ independent manner [181]. Soluble CD93 then acts as an opsonin-coating apoptotic cells and is in turn bound by a x b 2 integrin on macrophages via the CD93 EGF repeats aiding phagocytosis.…”
Section: Cd93 Sheddingmentioning
confidence: 99%